2006
DOI: 10.1007/s00418-005-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of matrix Gla protein in a marine cartilaginous fish, Prionace glauca: preferential protein accumulation in skeletal and vascular systems

Abstract: Matrix Gla protein (MGP) belongs to the family of vitamin K dependent, Gla containing proteins and, in mammals, birds and Xenopus, its mRNA has been previously detected in bone, cartilage and soft tissue extracts, while the accumulation of the protein was found mainly in calcified tissues. More recently, the MGP gene expression was also studied in marine teleost fish where it was found to be associated with chondrocytes, smooth muscle and endothelial cells. To date no information is available on the sites of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
(39 reference statements)
2
20
0
Order By: Relevance
“…Our results confirm previous reports of Mgp accumulation in kidney by Ortiz-Delgado et al (2006) for blue shark and Zhao and Nishimoto (1996) for rat. The fact that only few articles report this accumulation might be the time scale of Mgp expression/accumulation in kidney, as demonstrated by Zhao and Nishimoto, 1996, and/or the possibility that the need for this protein in kidney may vary among species.…”
Section: In Soft Tissues Mgp Accumulates Essentially In Heart and Kisupporting
confidence: 93%
See 1 more Smart Citation
“…Our results confirm previous reports of Mgp accumulation in kidney by Ortiz-Delgado et al (2006) for blue shark and Zhao and Nishimoto (1996) for rat. The fact that only few articles report this accumulation might be the time scale of Mgp expression/accumulation in kidney, as demonstrated by Zhao and Nishimoto, 1996, and/or the possibility that the need for this protein in kidney may vary among species.…”
Section: In Soft Tissues Mgp Accumulates Essentially In Heart and Kisupporting
confidence: 93%
“…Our results by in situ hybridization confirmed that cardiomyocytes were expressing mgp. Furthermore, localization of mgp mRNA in cardiac structures by in situ hybridization was also previously shown to occur in fish by our group (Gavaia et al, 2006;Ortiz-Delgado et al, 2006;Pinto et al, 2003). The presence of high levels of mgp in heart tissue is indicative of its function as a calcification inhibitor since this tissue has been shown to be a target of ectopic calcifications during pathological conditions, where expression and/or function of mgp is altered (Jono et al, 2006;Luo et al, 1997;Proudfoot and Shanahan, 2006;Schurgers et al, 2005).…”
Section: The Highest Levels Of Turbot Mgp Gene Expression Are Found Isupporting
confidence: 52%
“…Peroxidase activity was detected using as secondary antibodies the peroxidase-conjugated goat anti-rabbit and anti-mouse IgG, respectively (SigmaAldrich), and 0.025% 3,3-diaminobenzidine (SigmaAldrich) as described. 20,21 Negative controls consisted in the substitution of the primary antibody with both normal rabbit serum and CBT. Counterstaining was performed with hematoxylin and eosin or toluidine blue.…”
Section: Immunolocalizationmentioning
confidence: 99%
“…20,21 Briefly, the endogenous peroxidase activity was blocked with 3% H 2 O 2 in Coons buffer (CBT: 0.1 mol/L Veronal, 0.15 mol/L NaCl, 0.1% Triton X-100) for 15 minutes. Nonspecific antibody binding was blocked with 0.5% (w/v) bovine serum albumin directly after peroxidase activity blocking, or after treatment with chondroitinase ABC (Sigma-Aldrich) (0.1 U/ml) for 1 hour at 37°C.…”
Section: Immunolocalizationmentioning
confidence: 99%
“…Finally, Ortiz-Delgado et al (2005) used a teleost Wsh model of tooth development to examine the tissue distribution and accumulation of osteocalcin [also known as bone Gla protein (BGP)] and matrix Gla protein (MGP). In continuation of these studies, the authors (Ortiz-Delgado et al 2006) investigated the sites of MGP gene expression and protein accumulation by in situ hybridization and immunohistochemistry. MGP mRNA and protein were localized as expected not only in cartilage from branchial arches and vertebra but also in the endothelia of the vascular system as well as in the tubular renal endothelium.…”
Section: New Developments In Developmental Biology Diverentiation Rmentioning
confidence: 98%